PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP MINAT BELI PRODUK BATIK JETIS DI SIDOARJO - Ike Susanti; Ratna Handayati (ITB AAS INDONESIA Surakarta, 2021)
Batik is one of the ancestral cultural heritage of Indonesia. With the diversity of batik patterns, it is able to attract the attention of the world through its characteristics. Several regions in Indonesia have become centers of batik production, one of which is Jetis Village in Sidoarjo sub-district, Sidoarjo district, East Java. The increasingly sharp competition in batik production encourages batik craftsmen to always maintain the price of batik and the quality of batik in order to be able to compete with batik from various other regions, both in the local market and in the international market. Methods This research uses quantitative methods which are carried out by distributing questionnaires as respondent data. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple correlation, coefficient of determination, multiple linear regression analysis, t test and F test, data processing using SPSS statistical program. The conclusion of the research shows that price and product quality have a significant and positive effect on consumer buying interest in Batik Jetis products. Promotion is the most dominant product. Judging from R2 of 79.2 percent, it can be concluded that the production diversification of 79.2 percent of the variables can be determined from the predictive variable, while the remaining 20.8 percent is determined by other factors. Keywords: Product Quality, Price, Promotion, Buying Interest